Special legal feature of Islamic wa'd or pledge: comparison with the conventional law on promise within the sphere of Islamic finance - Wisham, Ismail; Muneeza, Aishath; Hassan, Rusni (Emerald Group Publishing Limited, 2011)
Purpose – The purpose of this paper is to theoretically assess the legal position of the Islamic doctrine of wa'd (or pledge) in relation to 'aqd (within the sphere of Islamic finance), and compare it with the conventional viewpoint, while discussing the several modes/means/usages in terms of applied Shariah.